Identification of a Novel Cis-Acting Regulator of HIV-1 Genome Packaging - Sakuragi, Sayuri; Kotani, Osamu; Yokoyama, Masaru; Shioda, Tatsuo; Sato, Hironori; Sakuragi, Jun-ichi (International journal of molecular sciences, 2021)
Human immunodeficiency virus type 1 (HIV-1) uptakes homo-dimerized viral RNA genome into its own particle. A cis-acting viral RNA segment responsible for this event, termed packaging signal (psi), is located at the 5′-end of the viral genome. Although the psi segment exhibits nucleotide variation in nature, its effects on the psi function largely remain unknown. Here we show that a psi sequence from an HIV-1 regional variant, subtype D, has a lower packaging ability compared with that from another regional variant, HIV-1 subtype B, despite maintaining similar genome dimerization activities. A series of molecular genetic investigations narrowed down the responsible element of the selective attenuation to the two sequential nucleotides at positions 226 and 227 in the psi segment. Molecular dynamics simulations predicted that the dinucleotide substitution alters structural dynamics, fold, and hydrogen-bond networks primarily of the psi-SL2 element that contains the binding interface of viral nucleocapsid protein for the genome packaging. In contrast, such structural changes were minimal within the SL1 element involved in genome dimerization. These results suggest that the psi 226/227 dinucleotide pair functions as a cis-acting regulator to control the psi structure to selectively tune the efficiency of packaging, but not dimerization of highly variable HIV-1 genomes.